COVID‐19 outcomes of patients with gynecologic cancer in New York City. Issue 19 (30th July 2020) - Lara, Olivia D.; O'Cearbhaill, Roisin E.; Smith, Maria J.; Sutter, Megan E.; Knisely, Anne; McEachron, Jennifer; Gabor, Lisa R.; Jee, Justin; Fehniger, Julia E.; Lee, Yi‐Chun; Isani, Sara S.; Wright, Jason D.; et al.
Abstract : Background: New York City (NYC) is the epicenter of severe acute respiratory syndrome coronavirus 2 (coronavirus disease 2019 [COVID‐19]) in the United States. Clinical characteristics and outcomes of vulnerable populations, such as those with gynecologic cancer who develop COVID‐19 infections, is limited. Methods: Patients from 6 NYC‐area hospital systems with known gynecologic cancer and a COVID‐19 diagnosis were identified. Demographic and clinical outcome data were abstracted through a review of electronic medical records. Results: Records for 121 patients with gynecologic cancer and COVID‐19 were abstracted; the median age at the COVID‐19 diagnosis was 64.0 years (interquartile range, 51.0‐73.0 years). Sixty‐six of the 121 patients (54.5%) required hospitalization; among the hospitalized patients, 45 (68.2%) required respiratory intervention, 20 (30.3%) were admitted to the intensive care unit, and 9 (13.6%) underwent invasive mechanical ventilation. Seventeen patients (14.0%) died of COVID‐19 complications. No patient requiring mechanical ventilation survived. On multivariable analysis, hospitalization was associated with an age ≥64 years (risk ratio [RR], 1.73; 95% confidence interval [CI], 1.18‐2.51), African American race (RR, 1.56; 95% CI, 1.13‐2.15), and 3 or more comorbidities (RR, 1.43; 95% CI, 1.03‐1.98). Only recent immunotherapy use (RR, 3.49; 95% CI, 1.08‐11.27) was associated with death due to COVID‐19 on multivariable analysis; chemotherapy treatment and recent major surgery were not predictive of COVID‐19 severity or mortality. Conclusions: The case fatality rate among gynecologic oncology patients with a COVID‐19 infection is 14.0%. Recent immunotherapy use is associated with an increased risk of mortality related to COVID‐19 infection. Lay Summary: The case fatality rate among gynecologic oncology patients with a coronavirus disease 2019 (COVID‐19) infection is 14.0%; there is no association between cytotoxic chemotherapy and cancer‐directed surgery and COVID‐19 severity or death. As such, patients can be counseled regarding the safety of continued anticancer treatments during the pandemic. This is important because the ability to continue cancer therapies for cancer control and cure is critical. Abstract : The case fatality rate among gynecologic oncology patients with a coronavirus disease 2019 (COVID‐19) infection is 14.0%. There is no association between cytotoxic chemotherapy and cancer‐directed surgery and COVID‐19 severity or death.